2004
DOI: 10.1136/gut.2004.042317
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline increases arginine pools and restores nitrogen balance after massive intestinal resection

Abstract: Objective: Arginine supplementation seems logical in situations where this amino acid becomes essential, for example after massive intestinal resection. Arginine is taken up and metabolised by the liver to a large extent and its supplementation is potentially unsafe. Citrulline is not captured by the liver and passes freely to the kidneys where it is metabolised to arginine, and so is a good candidate to generate arginine and thereby improve nutritional status. Methods: Twenty four rats were assigned to four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
3
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(118 citation statements)
references
References 34 publications
6
106
3
3
Order By: Relevance
“…Thereafter, the bulk of plasma Cit is converted to Arg, mostly in the kidneys (15,24,59,65,70), but also in several other tissues (15,23,70). This is compatible with the significant increase in plasma [Arg] in this study and several previous studies (32,47,53,62) following Cit supplementation. It is important to note that not only does Cit increase systemic [Arg] by avoiding catabolism along the intestinal-renal axis, but Cit might also be expected to enhance Arg bioavailability, given that Cit can function as an allosteric inhibitor of arginase (54).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thereafter, the bulk of plasma Cit is converted to Arg, mostly in the kidneys (15,24,59,65,70), but also in several other tissues (15,23,70). This is compatible with the significant increase in plasma [Arg] in this study and several previous studies (32,47,53,62) following Cit supplementation. It is important to note that not only does Cit increase systemic [Arg] by avoiding catabolism along the intestinal-renal axis, but Cit might also be expected to enhance Arg bioavailability, given that Cit can function as an allosteric inhibitor of arginase (54).…”
Section: Discussionsupporting
confidence: 81%
“…This is supported by our finding of a lower plasma [Orn], the product of Arg metabolism by arginase (70), after Cit than Arg supplementation in this study. However, despite this potential for greater systemic Arg bioavailability following oral Cit than oral Arg supplementation and in contrast to previous studies reporting a greater increase in plasma [Arg] after Cit than Arg ingestion (32,47,53,62), plasma [Arg] was increased by a similar magnitude when the same dose of Cit and Arg was orally administered in this study. These conflicting findings might be a function of between-study differences in the experimental subjects and supplementation regimens.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although traditionally recognised as a product of the nitric oxide synthase-mediated oxidation of L-arginine [3], recent evidence suggests that L-citrulline can be recycled back to L-arginine [17] and is more effective than orally ingested L-arginine at increasing systemic [18,19] and muscle [20] L-arginine.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal dysfunction resulting from intestinal diseases or injuries affect intermediary and inter-organ metabolism [83][84][85] . Hence, any factor affecting the intestinal mucosal cell mass will have an impact on protein and amino acid metabolism [83,[86][87][88][89][90] . Since the pioneering work of Windmueller and Spaeth during the 1970's many research groups have demonstrated that amino acids are the major fuel for the small bowel epithelium, both under conditions of fasting and feeding [91][92][93][94][95][96][97] .…”
Section: Small Intestinal Intermediary Metabolismmentioning
confidence: 99%